Compliance costs of goods and services tax (GST) among small and medium enterprises - Rosiati Ramli,; Mohd Rizal Palil,; Norul Syuhada Abu Hassan,; Ahmad Fariq Mustapha, (Penerbit Universiti Kebangsaan Malaysia, 2015)
Taxation is one of the most important instruments in generating revenue for a country. History has shown that many countries develop based on tax revenue. Tax- based spending, also known as Goods and Services Tax (GST) or Value Added Tax (VAT) is a consumerism tax posed upon sales of goods and services. It is a potential tax instrument introduced by the Malaysian government in order to broaden and increase tax collection. The implementation of GST in Malaysia is a unique case in which it will replace service and sales taxes. The introduction of GST has had people from all walks of life, from academicians, professionals to the people (taxpayers), debating about the effect of increasing price and decreasing sales and services tax. The Malaysian government expects the GST to minimise individual and corporate tax rates in order to reduce tax liabilities in both entities. Small and medium enterprises (SMEs) are among the focal point of discussion related to the compliance cost of GST. The compliance cost of SMEs is expected to increase as soon as GST is implemented. As the profit of SMEs is relatively low, would they be able to adopt the initial compliance costs of GST efficiently at the time of its implementation? If the SMEs are receptive towards GST, how much are the compliance costs through new development of software system, training of human resources and new accounting system? The International Monetary Fund (IMF) believed that the Malaysian tax system could be enhanced (increased tax collection) by introducing GST. There are two main objectives of this study; first is to identify the compliance costs of SMEs in fulfilling their tax obligations; and second to investigate the expected costs and readiness of these companies in the implementation of GST. In achieving these two objectives, the data were collected from SMEs by using structured questionnaires. This study is significant as it estimates the compliance costs among SMEs as well as outlining recommendations and suggestions to tax administrators so that they could consider the tax liability and compliance cost in their daily operation.